Implementation of Numbered Head Together Assisted by Number Card Media to Improve the Ability to Recognize Number Symbols at Al-Barokah Kindergarten Jambi City - Shalsha Widianti; Dian Syafitrah; Mukhlas Nugraha; Mardiana Mardiana; Mastikawati Mastikawati; Munawaroh Munawaroh (Universitas Muhammadiyah Enrekang, 2024)
This research aims to improve the ability of early childhood students to recognize number symbols through the implementation of the numbered head together method assisted by number card media at Al-Barokah Kindergarten, Jambi City. The background of this study is the low ability of children to recognize number symbols, including counting concrete objects, identifying numbers according to their symbols, and calculating quantities. Based on initial observations, the majority of children were at the